Solid organ transplantation medicine in Arab countries: A Narrative Review Focused on Ethical Aspects - Bel’eed-Akkari, Khalid; Hafidh, Khadija; Hajjaji, Issam; Beshyah, Salem; Elkhammas, Elmahdi (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Introduction: Ethical issues have been at the center of transplantation medicine for the past 60 years. Arab countries are not without ethical concerns with living donations as the dominant type of organ source. There is no comprehensive review of the ethical consideration evolvement. This narrative review aims to examine the English medical literature over the past 25 years. Materials and Methods: This is a narrative review of the international literature from two online databases (PubMed and Scopus). The combined search term “Ethics and Transplantation” was coupled with the individual names of the countries of the Arab countries. Relevant literature was narrated in a concise thematic account. Results: The themes that emerged from the review process included global concern on transplantation ethics that touched on the Middle East and North Africa (MENA) region. Some reports on transplantation practice status in the MENA region address clinical practice, organization, and ethical considerations. Organ-specific reports focused on renal and liver transplantation. Several other researchers addressed the knowledge and attitudes of health-care professionals of transplantation and posttransplantation care. The ethics of transplantation medicine has focused on the donation and financially motivated provision of organs (mainly kidneys). A few authors have underscored the implications of the Istanbul declaration on the prevention of trafficking of human organs to the practice of transplant medicine. Being a Muslim-majority region, several authors addressed the ethical and medicolegal aspects of transplantation from an Islamic perspective. Conclusions: Ethical issues in transplantation are evolving in Arab countries. They are mostly related to religious and cultural backgrounds. A broader dialog between the medical community, Islamic scholars, and legislators must continue to align concepts such as brain death and donor compensation. Furthermore, a concerted effort is required to inform the public and further the transplant agenda.
Keywords: Arab countries; ethics; Islamic; kidney; liver; medico-legal; middle east; North Africa; organ donation; organ transplantation; review